Effect of Viligen™, Feed Form, and Storage Time on Fumonisin Concentrations in Corn - Z. X. Rao; M. D. Tokach; S. S. Dritz; J. C. Woodworth; J. M. DeRouchey; R. D. Goodband; H. Calderon Cartagena (Kansas Agricultural Experiment Station Research Reports, 2019)
This trial was conducted to determine the effect of ViligenTM(Alltech, Lexington, KY), feed form (meal or pelleted) and storage time (0, 3, or 7 d) on reducing the fumonisin (FUM) concentration in diets. Three 1,000-lb batches of feed were manufactured and used as replications. Each batch was divided into 500-lb batches with or without Viligen at 0.15% of the diet. Diets were then left as a meal or pelleted and stored at room temperature for 0, 3, and 7 d to determine the reduction of FUM over time. The result indicated that there were no main or interactive effects (P>0.05) of Viligen, feed form, and storage time. There were marginal (P<0.10) 3- and 2-way interactive effects, but the magnitude of response likely was not large enough to have biological effects on nursery pig performance.
Keywords: fumonisin (FUM); Viligen; feed form; storage time